EXPERIMENT AND RESEARCH ON TRACTION GEARBOX HOUSING IN HIGH-SPEED TRAIN BASED ON TEST BENCH - RU XueBin; WANG GangQiang; LAI YuBin; ZHU WanGang (Jixie qiangdu)
The experiment on vibration,acoustic noise and stress of gearbox housing in high-speed train under various work condition was determined and experimental test was carried out on test bench according to the characteristic of gearbox housing.The results revealed that amplitude of acceleration,value of air noise and stress increased with the rotating speed increased when rated load remained constant. The value of acceleration of gearbox reached the greatest when the rotating speed is 2 500 r/min or3 500 r/min. The vibration of gearbox housing was caused by engagement frequency and multiplication frequency according to the frequency domain analysis of acceleration and air noise under the rated rotating speed and load was constant,and there was sideband near to engagement frequency and multiplication frequency which frequency interval was the rotating frequency of the output shaft and input shaft. The maximum value of air noise is 89. 74 dB which occurred around the frequency of 2 400 Hz,it meets the engagement frequency of 2 391. 7 Hz. The experimental results can provide experimental data for the theoretical analysis of the gearbox housing.